KOMBINASI ALGORITMA KRIFTOGRAFI CAESAR CIPHER DAN PERMUTATION CIPHER UNTUK PESAN TEKS MENGGUNAKAN PYTHON - Sihombing, Riyan Feraldi; Khairuna, Aida; Hasan, Mhd Arief; Sembiring, Rafael Rezky; Ramadhan, Hardiansyah (Riau Journal Of Computer Science, 2021)
Currently, especially in the development of information technology is developing so rapidly. Safeguarding and protecting informational text messages from various parties that can harm is very important. Maintaining informed text messages has a science, like cryptography. Cryptography in text messages to protect important data so as not to harm the owner. Therefore, we need to improve text messaging, especially data such as document files and text messages. So, the authenticity of the data can be maintained safely. The combination of cryptographic algorithms used to secure text messages is the Caesar Cipher algorithm and the Permutation Cipher algorithm. So, by using a combination of the caesar cipher algorithm and the permutation cipher algorithm, the security level of text messages can be more maintained for the authenticity of the data.